ANALISIS FATWA (MUI) NO:106/DSN-MUI/X/2016 TERHADAP IMPLEMENTASI WAKAF ASURANSI DI LEMBAGA PRUDENTIAL INDONESIA - Zaini Abdul Malik; Ifa Hanifia Senjiati; Ibnu Muhammad Zibran; sabila azzahra (Prodi Hukum Keluarga Islam (Ahwal Asy-Syakhsiyyah) Fakultas Syariah Unisba, 2020)
ABSTRACTInsurance is a form of protection that is present either from the private sector or the government. One way of coverage in Indonesia is the Prudential institution. Prudential comes as an insurance option in which there is a waqf system. Asur waqf that serves for the overall benefit (virtue) of the people. The results show that Prudential comes with a variety of waqf insurance products with all applicable provisions, and is implemented on Islamic principles. The MUI fatwa analysis No. 106 of 2016 performed at the Prudential Insurance Institute found that discrepancies. Regarding endowment, up to 95% applies to the filing of new policies on PSBG and PSIA starting on January 10, 2019, with the condition that the leading participants have existing (conventional and sharia) systems that are still active. This action is not following fatwa no.106 / DSN-MUI / X / 2016, where insurance benefits may e represented at most 45% of the total insurance benefits.Keywords: Waqf, insurance policy, fatwa.